Regulation of expression of transcription factors nuclear factor-kappa B and early growth response-1 by Helicobacter pylori - Abdel-Latif, Mohamed Mahmoud Mohamed (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Pharmacology & Therapeutics, 2002)
The Gram-negative bacterium Helicobacter pylori colonizes the human gastric epithelium and is a causative agent of peptic ulcer disease and gastric adenocarcinoma. Although H. pylori colonization is associated with gastric inflammation, the pathogenic mechanisms remain poorly understood. H. pylori initiates an inflammatory and immune reaction within the gastric mucosa which subsequently leads to tissue injury. The induction of the host immune response elicits the production of many pro- inflammatory proteins such as cytokines, chemokines and adhesion molecules that are regulated at the transcriptional level. The results of this study provide a further understanding of the possible pathogenic mechanisms of H. pylori infection through initiation of the expression of the transcription factors nuclear factor-kappa B (NF-kB) and the early growth response factor-1 (Egr-1).
Keywords: Pharmacology & Therapeutics, Ph.D.; Ph.D. Trinity College Dublin